2003
DOI: 10.1098/rsta.2002.1152
|View full text |Cite
|
Sign up to set email alerts
|

Control of nucleation in glass ceramics

Abstract: Glass ceramics are advanced materials composed of one or more glass and crystal phases. By developing base glasses with appropriate compositions and by controlling crystal nucleation and growth in these glasses, glass ceramics with tailor-made properties can be fabricated. The key to developing this type of material is control of the nucleation processes. Both volume and surface nucleation can be exploited. Heterogeneous volume nucleation has been used to develop glass ceramics showing minimal thermal expansio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
81
1
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 159 publications
(90 citation statements)
references
References 19 publications
3
81
1
3
Order By: Relevance
“…Again, this gradual enlargement of the lithium metasilicates' peak intensities indicated that the development of lithium metasilicates was postulated to be temperature dependent and to involve the epitaxial growth of lithium metasilicate on a lithium orthophosphate crystal [32,55].…”
Section: The 750-780 °C Groupmentioning
confidence: 99%
“…Again, this gradual enlargement of the lithium metasilicates' peak intensities indicated that the development of lithium metasilicates was postulated to be temperature dependent and to involve the epitaxial growth of lithium metasilicate on a lithium orthophosphate crystal [32,55].…”
Section: The 750-780 °C Groupmentioning
confidence: 99%
“…These very small crystals in dental microstructures result in very special optical properties such as translucence and opalescence. Hence, the presence of these crystals in IPS d.SIGN also imparts these special optical properties to fluorapatite-leucite ceramic restorations 11) . As for the leucite crystals (less than 3 µm in diameter of flower-like morphology) also present in IPS d.SIGN ceramic, they contribute to the overall strength 12) .…”
Section: Introductionmentioning
confidence: 99%
“…It was possible to precipitate both lithium metasilicate, Li2SiO3, to develop Fotoform (R) or lithium disilicate , Li2Si2O5,to develop F otoceram(R) as devices for micromechanics (Beall[1]) .High strength glass-ceramics with flexural strength of 400 to 500 MPa were developed in multi -component glassceramics with the main crystal phase of lithium disilicate as a material with a self glazing effect (Echeverria [4]), or oriented crystals prepared by extrusion (Russel [5]) , or prepared by p ressing an SiO2-Al2O3-ZnO-Li2O-K2O-P2O5 glass-ceramic(Schweiger et al [6], HOland et al [7]) . Recently, the authors of this paper reported on nucleation ,phase formationand solid state reaction in a colored ZnO-free lithium disilicate glass -ceramic characterized by translucent properties and unexpected high flexural strength of more than 700 MP a (HOl and et al [8]).…”
Section: Introductionmentioning
confidence: 99%